The 18th Asian Games 2018 torch relay; Merpati Putih Denpasar ignites the spirit - I.B. Komang Surya Werdiyasa (Bali Tourism Board, 2018)
After waiting for 50 years, finally, Indonesia is going to host the 18th Asian Games 2018. In response to the mandate, the Indonesian government established INASGOC or Indonesia Asian Games 2018 Organizing Committee as the official committee, who is responsible for preparing all requirements for the event that lastly held in Indonesia in 1962. In welcoming the game, many projects are being conducted both in Jakarta as well as Palembang. Besides, a torch relay event is traveling throughout 54 cities and provinces in Indonesia, including Bali. It was launching from Yogyakarta on July 18, 2018, and it is scheduled to reach its finish point at Gelora Bung Karno on August 18, 2018. As a series of torch relay event visiting Bali, PPS Betako Merpati Putih, Branch Denpasar, one of the nation’s cultural assets, became one of sports training centers in Bali that had the opportunity to receive appreciation from PT Telkom Indonesia Tbk. Furthermore, all Indonesian citizen expect that Indonesian athletes can do their best in giving a contribution to the nation. Thus, Indonesia on the Asian games 2018 would be the host and house of the champion.